2020
DOI: 10.3389/fnut.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Traditional Ecological Knowledge and Access to Nutrient-Rich Indigenous Foods to Help Achieve SDG 2: An Analysis of the Indigenous Foods of Sauria Paharias, a Vulnerable Tribal Community in Jharkhand, India

Abstract: Ghosh-Jerath et al.Indigenous Foods of Sauria Paharias nutrient rich IFs and revival of little used IFs while addressing the causes of non-consumption and mainstreaming them into the daily diets could be an effective strategy to increase the intake of micronutrients. Policies focusing on incorporation of nutrient rich IFs into dietary diversification strategies and ongoing supplementary feeding programs can help address malnutrition in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…Many of the IFs reported in the study were found to be rich sources of proteins, vitamins and minerals especially iron, calcium, vitamin A, vitamin C and folic acid. The rich nutrient content of IFs consumed by Indian tribal communities have also been documented in other studies ( 23 , 40 , 45 , 67 , 68 ). A study on IFs of the Munda tribal community has documented consumption of some of the nutrient rich IFs in their routine diets.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Many of the IFs reported in the study were found to be rich sources of proteins, vitamins and minerals especially iron, calcium, vitamin A, vitamin C and folic acid. The rich nutrient content of IFs consumed by Indian tribal communities have also been documented in other studies ( 23 , 40 , 45 , 67 , 68 ). A study on IFs of the Munda tribal community has documented consumption of some of the nutrient rich IFs in their routine diets.…”
Section: Discussionsupporting
confidence: 78%
“…The community however, reported the historical cultivation and consumption of pearl millet, finger millet, little millet, and sorghum in the region. A similar trend on consumption of limited variety of cereals and diminishing consumption of diverse coarse cereals is observed in other tribal communities of Jharkhand as well as across India ( 23 , 40 , 57 ). Loss of coarse cereals like millets from the habitual Indian diet have been reported to have substantially reduced iron intake in the population, particularly in states where rice has replaced coarse cereals ( 58 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations